Review on Method Development and Validation of Remogliflozin Etabonate and Teneligliptin by RP-HPLC and UV Spectroscopy - Kedar Sneha Sanjay; Dr. Gaware Vinayak M. (Asian Journal of Pharmaceutical Research and Development, 2025)
The increasing global prevalence of Type 2 Diabetes Mellitus has driven the demand for safer and more effective therapeutic strategies, notably those combining novel antidiabetic agents. This study focuses on Remogliflozin Etabonate, a selective SGLT2 inhibitor, and Teneligliptin, a third-generation DPP-4 inhibitor, both offering complementary mechanisms for improved glycemic control. The research emphasizes the urgent need for robust analytical methods to ensure quality, safety, and efficacy of these drugs in pharmaceutical formulations. Various validated techniques including UV Spectroscopy, HPTLC, and RP-HPLC have been developed to accurately quantify these compounds. Among these, RP-HPLC stands out for its precision, reproducibility, and adaptability in routine analysis. Detailed method validation parameters such as linearity, accuracy, LOD, and LOQ are examined, supporting their compliance with ICH guidelines. This paper also compares the performance and suitability of existing methods while proposing optimal conditions for simultaneous estimation. The combination of Remogliflozin and Teneligliptin not only enhances therapeutic outcomes but also poses analytical challenges that are addressed through methodical development. The review underscores the significance of validated techniques in regulatory submissions and quality assurance, paving the way for advanced pharmacological monitoring. This comprehensive overview contributes to the evolving landscape of diabetes treatment and analytical innovation.